The Determinants of Salesperson Performance: A Meta-Analysis - Churchill, Gilbert A.; Ford, Neil M.; Hartley, Steven W.; Walker, Orville C. (Journal of Marketing Research, 1985)
The authors use meta-analysis techniques to investigate the evidence that has been gathered on the determinants of salespeople's performance. A search of the published and unpublished literature uncovered 116 articles (the list of which is available upon request) that yielded 1653 reported associations between performance and determinants of that performance. The results indicate the determinants can be ordered in the following way in terms of the average size of their association with performance: (1) role variables, (2) skill, (3) motivation, (4) personal factors, (5) aptitude, and (6) organizational/environmental factors. When ordered according to the amount of the observed variation in correlations across studies that is real variation (i.e., not attributable to sampling error), the determinants rank as follows: (1) personal factors, (2) skill, (3) role variables, (4) aptitude, (5) motivation, and (6) organizational/environmental factors. To investigate whether the associations between each of the categories of predictors and performance could be partially accounted for by the presence of moderator variables, the results were broken out by customer type, product type, and type of dependent measure used. The results indicate that the strength of the relationship between the major determinants and salespeople's performance is affected by the type of products salespeople sell. The authors discuss the implications of these findings for sales managers and researchers.